Visible-light-promoted radical cyclisation of unactivated alkenes in benzimidazoles: synthesis of difluoromethyl- and aryldifluoromethyl-substituted polycyclic imidazoles - Yujun Pang; Jinglan Yan; Nawaf Al-Maharik; Qian Zhang; Zeguo Fang; Dong Li (Beilstein Journal of Organic Chemistry)
An efficient and eco-friendly approach for synthesizing difluoromethyl- and aryldifluoromethyl-substituted polycyclic imidazoles was established via a visible-light-promoted radical cyclization reaction. This method employed the readily accessible and inexpensive CF2HCO2H or PhCF2COOH, along with benzimidazoles bearing unactivated alkenes and PhI(OAc)2 as substrates, and proceeded without the need of any base, metal catalyst, photocatalyst or additive. In total, 24 examples were examined, and all of them successfully underwent cyclization reaction to produce the target products in good to excellent yields. Mechanistic studies revealed that the reaction proceeds via a radical pathway.